EFEKTIVITAS PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II B MERAUKE - Erni Dwita Silambi; Marlyn Jane Alputila (Universitas Musamus, Merauke, Papua, 2015)
ABSTRACTPrevention of crime through the criminal law, an activity that preceded the determination of criminal acts and determination of the sanctions that can be imposed on the perpetrators of the crime or offense. Sanctions in criminal law is suffering as a reward of his actions that have hurt other people or society. Correctional as a coaching system that is essentially an activity that is multi dimensial, this is due to the recovery efforts unitary relationship of life, life and livelihood is a very complex issue. For it is necessary guidance to prisoners and correctional clients within a framework.However, in reality the convict after finished serving a prison sentence instead of a deterrent but instead repeat criminal offenses (recidivism). So in this case unquestionable effectiveness of coaching inmates in prisons class II B Merauke.This study juridical sociological. This research was conducted in the Penitentiary Class II B Merauke, namely data sources of primary data through observation and interviews and secondary data, legislation, books related to the research.Development patterns prisoners committed at the Correctional Institution Class IIB Merauke, divided into two (2) areas of the coaching personalities include: development of religious awareness, fostering awareness of state and nation, fostering intellectual abilities (intelligence), development of legal awareness, coaching integrate themselves with the community. Fostering Independence which include: skills to support the efforts of independent, skills to support the efforts of small industries, the skills developed in accordance with the talent of each, skills to support the efforts of industrial or agricultural activities (plantations) using technology associate.